Congenital Malformations in the Newborn Population: A Population Study and Analysis of the Effect of Sex and Prematurity - Alexander Egbe; Santosh Uppu; Simon Lee; Annemarie Stroustrup; Deborah Ho; Shubhika Srivastava (Pediatrics and Neonatology)
Congenital malformation (CM) is a leading cause of infant mortality. We hypothesized that the current estimates of the prevalence of CM are obsolete because of the increased rate of terminating fetuses with severe CMs and the widespread use of prenatal vitamins. Methods: This population-based cross-sectional study analyzed the effect of sex and prematurity on CM prevalence. All data were derived from birth entries in the 2008 Nationwide Inpatient Sample (NIS) database. Our objectives were to determine the prevalence of CM diagnoses among all birth hospitalizations in 2008 and to analyze the effect of sex and gestational maturity on CM prevalence. Results: We identified 29,312 patients with CMs from among 1,014,261 live births, which yielded a CM prevalence of 28.9 per 1000 live births. Associated genetic syndromes were present in 1172 (4%) patients. Among newborns with nonsyndromic CM, 91% of newborns had an isolated CM and 9% of newborns had multiple CMs. The cardiovascular system was the most commonly involved organ system. The risk of CM was significantly higher in preterm newborns for an isolated CM [odds ratio (OR), 1.5; confidence interval (CI), 1.4–1.5]; multiple CMs (OR, 2.1; CI, 2.0–2.3); and overall CMs (OR, 1.4; CI, 1.3–1.5). Males had higher risk of isolated CMs (OR, 1.3; CI, 1.2–1.5). However, there was no sex difference in the risk of overall CM. Conclusion: We reported up-to-date national estimates of the prevalence of CM, which is important for monitoring trends, determining service planning, and assessing disease burden because of congenital malformations in the United States of America. We also showed a strong association between CM and prematurity. Further study of this association is needed to provide insight into the etiology of these relatively common public health problems.